Student teachers' opportunities to learn through observation, own practice and feedback on the practice while in field practice placements: a graphical model approach - Tine Nielsen (EARLI, 2024)
Field practice placement is a crucial part of teacher education, as it affords a real-life context, where teacher and teacher-related skills can be enacted and trained. The present study examined the associations between student teacher opportunities to learn through observation, own practice and the receiving of feedback of said practice, while in field practice placements through a teacher education programme. Chain graph models were used to analyse data from 560 Danish student teachers who had just completed field practice at one of three levels. Results showed that opportunities to learn through observation of fellow students and other teachers was negatively associated with level of field practice, and thus was reported less and less the further along students were in the programme, while opportunities to learn through own practice was positively associated with level of field practice. Opportunities to learn through receiving feedback on own practice was associated with level of field practice only via opportunities to learn through own practice. Results did not reveal gender or age-wise inequity in the opportunities to learn afforded in the field practice. Teacher education programmes could benefit from placing additional focus on opportunities to learn through observation in the later field practice placements.